Landasan Teologi Ekonomi Islam: Peran Tauhid dan Keadilan dalam Mewujudkan Ekonomi yang Adil dan Sejahtera - Anggi Rizkina Sari Siregar; Namira Hamni Lubis; Nikita Adelia Syafitri; Ahmad Wahyudi Zein (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
This study analyzes the role of the concept of monotheism and justice in the Islamic economic system through a literature study. The focus of the study is to explore how theological foundations can transform the conventional economic paradigm into a more just and sustainable system. The results show that the integration of monotheism and justice creates an economic model that pays attention to material and spiritual welfare, with instruments such as zakat as a redistribution mechanism. The study identifies challenges in implementing Islamic economics and offers strengthening strategies through education, policy, and technological innovation. In conclusion, Islamic economics has the potential to present a more just and inclusive economic system in the modern era.